Reduction of Carbonyl Compounds with (±)-2-Trimethylsilyl-2,3-dicarba-nido-hexaborane(8) - Urs von Arx; Prakash R. Pradhan; Reinhart Keese (CHIMIA)
The racemic nido-carbaborane 1 reduces aldehydes and ketones but not styrene after addition of small amounts of water.